Design And Analysis Of A Series Active Power Filter Based On Hysteresis Controller For Power Quality Improvement - Hashim, Hadi Fakhir (2016)
This dissertation presents the analysis and design of a three phase series active power filter based on hysteresis controller for power quality improvement. The proposed system comprises of a filtering scheme, injection transformer, Voltage Source Inverter (VSI) and its controller. The main aim of this dissertation covers design, analysis and modeling using MATLAB/SIMULINK for a three phase series active power filter. The system is capable of mitigating voltage sags and swells at low voltage distribution system. The proposed controller based on hysteresis controller was applied to the series active power filter throughout injected transformer. The implementation of hysteresis controller is capable to detect voltage disturbances in supply voltage and injects an appropriate voltage in order to recover decrease or an increase of supply voltage back to its nominal value, and then the load can be protected from any voltage disturbances. The connected load in the system consists of linear or nonlinear loads. The Total Harmonics Distortion (THD) values of current and voltage for linear and non-linear loads are measured. The various performances of simulation results of the proposed modeling has been investigated. Finally, the proposed system has successfully implemented in this research for mitigating voltage sags and swells. In addition, the voltage disturbance compensating performance of the Series Active Power Filter has improved using the hysteresis-control method.